THE ASSESSMENT OF JAPANESE RESTAURANT IN BANDUNG SERVICE QUALITY AND ITS IMPLICATION ON CUSTOMER SATISFACTION - Yudha, Jerry Pima; Belgiawan, Prawira Fajarindra (Journal of Business and Management, 2018)
Abstract. Background: Japanese Restaurants has grown well in Indonesia, especially in Bandung. One of them is Restaurant X which very well-known in the society. There are numerous elements in a restaurant, but previous researches have found that service quality is one of the most important. The objective of this research is to measure the current state of service quality at Restaurant X and to find out whether it has a significant influence on customer satisfaction. Methods: Data analysis used are student t-test and multiple linear regressions method. This research measured the current state of service quality at Restaurant X by calculating the significant difference between customer expectation and customer perception. Results: There is a significant difference between customer expectation and customer perception in all service quality dimensions which are tangibles, reliability, responsiveness, assurance, and empathy. The result also showed that tangibles, responsiveness, and empathy dimension have a significant correlation with customer satisfaction, meanwhile, reliability and assurance dimension does not have. Conclusion: Restaurant X need to improve their service quality thoroughly since it does not meet customer expectation in any dimension. In its application, Restaurant X can focus on tangibles, responsiveness, and empathy dimension first since those dimensions have correlations with customer satisfaction.Keywords: customer expectation, customer perception, customer satisfaction, Japanese Restaurant, service quality,